Power-carbon coordinated control of BFG-fired CCGT power plant integrated with solvent-based post-combustion CO2 capture. (1st July 2021) - Wu, Xiao; Xi, Han; Ren, Yuning; Lee, Kwang Y.
Abstract: Decarbonizing the energy intensive iron and steel industry is in urgent need to meet the ambitious environmental goal. Efficient and clean use of the blast furnace gas (BFG) through combined-cycle gas turbine (CCGT) power plant provides feasible pathway to realize a near-term CO2 reduction when integrated with carbon capture. This paper presents effective control strategies to coordinate the operation of BFG-fired CCGT plant and solvent-based post-combustion CO2 capture (PCC) process based on the in-depth understanding of the interactions among process dynamics in different time-scales for carbon, heat and electricity. The energy storage capability of the PCC process is explored in addition to the CO2 capture and the reboiler steam flowrate used for solvent regeneration is incorporated into the BFG-fired CCGT control loop. Considering this, two coordinated control strategies are developed for the BFG-fired CCGT-PCC, first based on the conventional PI control and then with advanced model predictive control (MPC) approaches. The coordinated strategies are demonstrated to improve the power ramping performance of the CCGT with little degradation on the PCC operation, thus providing better support for the reliability of the power system in the context of increasing penetration of renewable energy resources. Moreover, by considering the impact of disturbances into the predictive models, the MPC-based coordinated control can well alleviate the influence of BFG fluctuations, guaranteeing a stable operation of the integrated plant. This paper points to the new direction of using PCC for more flexible power regulation of adjustable sources in low-carbon energy systems with penetration of intermittent renewable powers. Graphical abstract: Image 1 Highlights: Dynamic modelling of the BFG-fired CCGT-PCC plant. The time scale features of gas turbine, steam generator-turbine and PCC are explored. Coordinated control of the BFG-fired CCGT-PCC plant using PI and MPC. Couplings among carbon, heat and electricity are exploited to coordinate the control. Disturbance rejection operating control in the presence of BFG fluctuations.